China Cloud Rising China's Journey Towards Technology Supremacy - Zhu, Jinzy; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
In twenty years, China's expenditures for research and development will surpass those of the United States, a trend that epitomizes nationalistic ambitions to regain intellectual prestige for a country that had once invented paper and gunpowder. Tens of billions of dollars have been poured into a new technology superstructure as China seeks to transform its economy from a crippling reliance on manufacturing outsourcing. Cloud computing represents a dynamic foundation for the new superstructure that can foster the growth of a socio-capitalistic ecosystem, creating a new class of green exports in the form of highly sophisticated software and services. With Cloud computing, China is seeking to establish a new Silk Road, where its cultural products will once again change the world.
Cloud Evolution -- Cloudonomics -- Cloud Security -- Cloud Standards -- China Dreams -- Connecting the Possibilities -- Cloud Use Cases -- China Firsts -- Cloud in Motion -- Clouds of Change -- Cloud Factory -- The Art of Cloud Wars.
Keywords: Economics; Economics/Management Science; Economics/Management Science, general